2008
DOI: 10.1021/jf800268t
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Furan and Methylfuran by Maillard-Type Reactions in Model Systems and Food

Abstract: The formation of furan and 2-methylfuran was studied in model systems based on sugars and selected amino acids. Both compounds were preferably formed under roasting conditions in closed systems yielding up to 330 micromol of furan and 260 micromol of 2-methylfuran per mol of precursor. The amounts obtained under pressure cooking conditions were much lower, usually below 20 micromol/mol, except for 2-furaldehyde, which yielded 70-100 micromol/mol of furan. Labeling studies indicated two major formation pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
180
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(201 citation statements)
references
References 16 publications
15
180
2
4
Order By: Relevance
“…This work can be considered as another milestone in the history of research on Maillard chemistry. The CAMOLA technique has recently also been applied for studying the formation of furan in both model systems and foodstuffs (Limacher et al, 2008).…”
Section: General Aspects Of the Maillard Reaction Cascadementioning
confidence: 99%
“…This work can be considered as another milestone in the history of research on Maillard chemistry. The CAMOLA technique has recently also been applied for studying the formation of furan in both model systems and foodstuffs (Limacher et al, 2008).…”
Section: General Aspects Of the Maillard Reaction Cascadementioning
confidence: 99%
“…The presence of alanine, threonine, or serine promoted the furan formation by recombination of C 2 fragments, such as acetaldehyde and glycolaldehyde, which might originate from both sugars and amino acids. In the aqueous solution, about a half of furan was generated by the recombination of the sugar fragments (Limacher et al 2008).…”
Section: Furan Formation Through Carbohydrate Degradationmentioning
confidence: 99%
“…The diversity of foods which contain furan suggests that multiple pathways are likely to be involved in the formation of furan in foods (Morehouse et al 2007;Owczarek-Fendor et al 2011;. Studies performed in model systems have shown that furan and methylfuran can be generated from heating ascorbic acid, polyunsaturated fatty acids, unsaturated aldehydes, sugars, and amino acids (Perez & Yalayan 2004;Becalski & Slaman 2005;Limacher et al 2007;Limacher 2008;Roberts et al 2008;Vranová & Ciesarová 2009;Owczarek-Fendor et al 2010a,b, 2012Adams et al 2011;Duan & Barringer 2012;Anese & Suman 2013).…”
mentioning
confidence: 99%